Conjunctival Collagen Cross-Linking for the Treatment of Leaking Avascular Cystic Bleb - Ali Mert Koçer; Büşra Turpçuoğlu (Türk Oftalmoloji Dergisi)
Trabeculectomy is a primary surgical procedure used to reduce intraocular pressure (IOP) in patients with glaucoma. Despite its effectiveness, it can lead to significant complications, including hypotony, choroidal effusion, blebitis, and bleb leaks. Bleb leaks require prompt medical or surgical intervention to prevent severe complications such as blebitis and bleb-associated endophthalmitis. In recent years, the indications for collagen cross-linking (CCL) have expanded beyond corneal ectatic diseases to include various ocular conditions such as keratitis and leaking blebs. Here, we present the case of a 70-year-old male patient with a leaking avascular cystic bleb. Following treatment with a combination of conjunctival CCL, topical gentamicin, a dorzolamide/timolol combination, and a therapeutic contact lens, the patient experienced cessation of bleb leakage and an increase in IOP.